Acute Alcohol Binge Deteriorates Metabolic and Respiratory Compensation Capability After Blunt Chest Trauma Followed by Hemorrhagic ShockA New Research Model - Wagner, Nils; Franz, Niklas; Dieteren, Scott; Perl, Mario; Moers, Katharina; Marzi, Ingo; Relja, Borna (Alcoholism-Clinical and Experimental Research, 2017)
BackgroundThe clinical relevance of blunt (thoracic) chest trauma (TxT) and hemorrhagic shock is indisputable due to the high prevalence of this injury type, as well as its close association with mortality and/or preventable deaths. Furthermore, there is an ongoing discussion about the influence of alcohol in trauma patients. Thus, we established a model of TxT followed by hemorrhagic shock with resuscitation (H/R) in alcohol-intoxicated rats.MethodsDepending on group allocation, 12 (subacute) or 2 (acute) hours before experimentation, the animals received a single oral dose of alcohol (ethanol [EtOH]) or saline (NaCl) followed by TxT, hemorrhagic shock (353mm Hg), and resuscitation (TxT+H/R). Arterial blood gas analyses and continuous monitoring of blood pressure were performed during the experimentation period. Survival during the experimentation procedure was determined.ResultsSubacute and acute EtOH group exhibited lower baseline mean arterial blood pressure values compared with the corresponding NaCl group, respectively. Both EtOH groups showed lower maximal bleed-out volume, which was necessary to induce hemorrhagic shock compared to NaCl groups, and the recovery during the resuscitation period was attenuated. During the experimentation in all groups, a trend to acidic pH was observed. Acute EtOH group showed lowest pH values compared to all other groups. Higher pCO(2) values were observed in both EtOH groups. All groups developed negative base excess and decreasing HCO3- values until the end of hemorrhagic shock and showed increasing base excess and HCO3- values during resuscitation. Significantly higher mortality rate was found in the acute EtOH group.ConclusionsThis study indicates that alcohol limits the metabolic and respiratory compensation capability, thereby promoting mortality.
Keywords: Alcohol; Binge; Acidosis; Respiratory; Metabolic; Blood Gas Analyses